The Revised Trauma Score: A Better Early Predictor for Survival of Head Trauma Patients than the Glasgow Coma Scale-Age-Pressure Score - Richa Patel; Geeta Sandeep Ghag; Sandhya Iyer; Vipul Versi Nandu (Journal of Acute Care Surgery)
Purpose Trauma is a common cause of death worldwide and head injury is the most common form of trauma presented at the Emergency Department. Physiological scores are better for predicting outcome than anatomical scores. To reduce mortality rates, this study compared the capacity of the revised trauma scores (RTS) and the Glasgow coma scale- age- pressure (GAP) scores to predict the survival of patients and effectively channel resources. Methods An observational study of head trauma patients aged 12 to 80 years was performed at a tertiary care center (N = 500). We noted demographic information, RTS and GAP trauma scores, and outcomes in terms of mortality or survival at 24 hours, 48 hours, and 7 days. Results Of the 500 patients who were enrolled, 414 (82.8%) survived 24 hours, 373 (74.6%) survived 48 hours, and 265 (53%) survived after 7 days. Using the Receiver Operating Characteristic curve, the RTS score was a significantly better predictor of survival in patients with head trauma than the GAP score at 24 hours (p = 0.044) and 48 hours (p = 0.049) of admission. The results were not significantly different at 7 days (p = 0.240). Mortality or survival outcomes were not significantly different between the RTS and GAP scores (p = 0.373). Conclusion RTS appears to be a better early predictor for mortality (within 48 hours of admission) than the GAP score. The RTS was more effective in directing the triage of patients which improved survival rates in head trauma patients.